2010
DOI: 10.3177/jnsv.56.104
|View full text |Cite
|
Sign up to set email alerts
|

Bolus Oral or Continuous Intestinal Amino Acids Reduce Hypothermia during Anesthesia in Rats

Abstract: SummaryWe hypothesized that, with oral or intestinal administration of amino acids (AA), we may reduce hypothermia during general anesthesia as effectively as with intravenous AA. We, therefore, examined the effect of bolus oral and continuous intestinal AA in preventing hypothermia in rats. Male Wistar rats were anesthetized with sevoflurane for induction and with propofol for maintenance. In the first experiment, 30 min before anesthesia, rats received one bolus 42 mL/kg of AA solution

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 26 publications
(21 reference statements)
2
8
0
Order By: Relevance
“…In the sham-operated rats, however, the inhibitory effect of amino acid infusion on hypothermia was not seen. In other studies done in male rats, amino acid infusion had a significant inhibitory effect on hypothermia, as measured by central body temperature, during general anesthesia (7,8,12,13). The results of our study suggest that in rats, ovarian function or female hormone decreases the inhibitory effect of amino acid infusion on anesthesia-induced hypothermia.…”
Section: Discussionsupporting
confidence: 58%
“…In the sham-operated rats, however, the inhibitory effect of amino acid infusion on hypothermia was not seen. In other studies done in male rats, amino acid infusion had a significant inhibitory effect on hypothermia, as measured by central body temperature, during general anesthesia (7,8,12,13). The results of our study suggest that in rats, ovarian function or female hormone decreases the inhibitory effect of amino acid infusion on anesthesia-induced hypothermia.…”
Section: Discussionsupporting
confidence: 58%
“…Intraoperative amino acid infusion exerts a marked thermogenic effect with enhanced oxygen consumption [2,3,4,5], mainly in the extra-splanchnic tissues, and significantly attenuates the decrease in core temperature during general anesthesia [6,7]. …”
Section: Introductionmentioning
confidence: 99%
“…However, rats in group C received 21 mL/kg of the carbohydrate-rich beverage, which corresponded to an energy content of 70.6 kJ/kg. In a previous study, we administered 70.6 kJ/kg of amino acid to rats and observed that this dose prevented hypothermia [10]. Although this dose seems much larger than the doses appropriate for humans, it should be considered that the rat metabolism is 5-7 times higher than that of humans, and that protein consumption by weight in rats is approximately 7 times that in humans [10].…”
Section: Methodsmentioning
confidence: 96%
“…Selldén et al [8,9] used another approach and reported that intravenous amino acid infusion prevents intraoperative hypothermia under general and spinal anesthesia. We also reported that preoperative oral amino acid intake contributes to the prevention of intraoperative hypothermia under general anesthesia in rats [10]. Mizobe et al [11] reported that preoperative fructose infusion helped to maintain normothermia by augmenting metabolic heat production and increasing the vasoconstriction threshold.…”
Section: Introductionmentioning
confidence: 94%